Brazil's landmark change on One Health, animal rights and protection - Vanessa Negrini; Paulo César Maiorka; Louise Bach Kmetiuk; Alexander Welker Biondo (One Health)
The Sustainable Development Goals (SDG) launched by the United Nations in 2015 were a global challenge calling for ending poverty, protecting the environment, and guaranteeing peace and prosperity to world citizens by 2030. Brazil has changed gears, accepted the SDG challenge and moved one step forward. On the dawn of January 1st, 2023, the very first day of President Lula's office, Brazil issued the Decree no. 11,349/2023 and created an additional SDG itself on animal health by establishing the Department of Animal Protection and Rights (DAPR). The DAPR primarily aims to establish a Federal Animal Code and other nationwide standard procedures for pet population management and mass neutering/spaying programs, services against animal cruelty, welfare meat production, meat substitutes, and enforcement of native fauna protection. Meanwhile, Brazil's new government has reduced in 48% the Amazon deforestation and mining, enforced the inspections on national parks and preserved areas, limited wild boar hunting. On top of it, Lula's G20 Bloc presidency starting this coming December has shown the Brazil commitment to reestablish its historical prominence on international conversation and diplomacy. Finally, recognition of a clear and unquestionable nexus among animal welfare, environment, and sustainability, beyond the United Nations original proposition, in a country level, particularly with still-preserved nature areas, should be understood and invested as humanity heritage.